Digital Leadership and Strategic Transformation: Unlocking the Competitive Potential of Digital Procurement - Saimon, Salauddin; Sogra, Syeda Morsheda; Abiodun, Olumuyiwa; Sogra, Syeda Faiza; Fard, Jalaleddin Kazemi (ExcelingTech, 2026)
Digital Procurement Transformation (DPT) is also taking the form of a strategic capability that transforms procurement into more of a value-generating centre in the supply chain ecosystem rather than a transactional and cost- oriented operation. The paper explores the management ambition and digital leadership which are driving DPT through testing a leadership-focused model that incorporates four enabling factors (digital strategy, skill upgradation, collaborative networks, and supply chain uncertainties) and four barrier factors (poor strategy, skill gaps, lack of collaboration, and supply chain barriers). The result, based on online survey of 50 international procurement and supply chain professionals and Partial Least Squares Structural Equation Modelling (PLS-SEM) is that collaborative network development and skill upgradation did have significant strengthening effect on management ambition, whereas poor digital strategy and lack of improvement in skills had their material weakening effect; on the contrary, digital strategy (as a direct facilitator) and supply chain uncertainties did not exhibit statistical significance in this model. The paper is valuable and directly contributed to vital information in terms of procurement leadership and digitalization, because it (i) empirically confirms a leadership-based DPT framework that simultaneously models enabling and inhibiting factors, (ii) pinpoints the organisational drivers that are most closely related to management ambition, and (iii) translates the findings into practical advice that procurement leaders should follow regarding adopting an ecosystem collaboration strategy, building workforce capabilities, and implementing a strategy.